Efficacy of Preemergence or Early Postemergence Weed Control with Keystone NXT, Hornet WDG, Atrazine, SureStart II, Lumax EZ, and Resicore - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2016)
Control of buffalobur was complete regardless of herbicide used. Velvetleaf and puncturevine control, although not perfect, was excellent by all herbicides. The premix of SureStart II (acetochlor + flumetsulam + clopyralid) with atrazine and Durango DMA (glyphosate) applied early postemergence and the preemergence herbicides Resicore (acetochlor + mesotrione + clopyralid) with atrazine and Lumax EZ (S-metolachlor + atrazine + mesotrione) provided excellent Palmer amaranth control. The early postemergence treatment of SureStart II plus atrazine and Durango DMA was the only treatment to provide excellent control of green foxtail.
Keywords: weed control; postemergence applications; velvetleaf; buffalo bur; Palmer amaranth; puncturevine; green foxtail; Keystone NXT; Acetochlor; Atrazine; Hornet WDG; Flumetsulam; Clopyralid; SureStart II; Lumax EZ; Mesotrione; Resicore; aminopyralid; 2; 4-D